Respiratory recovery trajectories after severe-to-critical COVID-19: a 1-year prospective multicentre study. Issue 4 (3rd April 2023) - Schlemmer, Frédéric; Valentin, Simon; Boyer, Laurent; Guillaumot, Anne; Chabot, François; Dupin, Clairelyne; Le Guen, Pierre; Lorillon, Gwenael; Bergeron, Anne; Basille, Damien; Delomez, Julia; Andrejak, Claire; et al.
Background: Survivors of severe-to-critical coronavirus disease 2019 (COVID-19) may have functional impairment, radiological sequelae and persistent symptoms requiring prolonged follow-up. This pragmatic study aimed to describe their clinical follow-up and determine their respiratory recovery trajectories, and the factors that could influence them and their health-related quality of life. Methods: Adults hospitalised for severe-to-critical COVID-19 were evaluated at 3 months and up to 12 months post-hospital discharge in this prospective, multicentre, cohort study. Results: Among 485 enrolled participants, 293 (60%) were reassessed at 6 months and 163 (35%) at 12 months; 89 (51%) and 47 (27%) of the 173 participants initially managed with standard oxygen were reassessed at 6 and 12 months, respectively. At 3 months, 34%, 70% and 56% of the participants had a restrictive lung defect, impaired diffusing capacity of the lung for carbon monoxide ( D LCO ) and significant radiological sequelae, respectively. During extended follow-up, both D LCO and forced vital capacity percentage predicted increased by means of +4 points at 6 months and +6 points at 12 months. Sex, body mass index, chronic respiratory disease, immunosuppression, pneumonia extent or corticosteroid use during acute COVID-19 and prolonged invasive mechanical ventilation (IMV) were associated with D LCO at 3 months, but not its trajectory thereafter. Among 475 (98%) patients with at least one chest computed tomography scan during follow-up, 196 (41%) had significant sequelae on their last images. Conclusions: Although pulmonary function and radiological abnormalities improved up to 1 year post-acute COVID-19, high percentages of severe-to-critical disease survivors, including a notable proportion of those managed with standard oxygen, had significant lung sequelae and residual symptoms justifying prolonged follow-up. Among a cohort of 485 survivors of severe-to-critical COVID-19, including non-ICU patients, most recovered well but a high percentage had residual radiological and functional sequelae, and residual symptoms up to 1 year, justifying prolonged follow-up https://bit.ly/3Zlm1fD